PENGARUH ARUS KAS OPERASI DAN FIXED ASSETS TURNOVER TERHADAP RETURN ON ASSETS (ROA) (STUDI KASUS PADA SEKTOR TELEKOMUNIKASI YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2009-2013) - Faisal Ahmad, Ferry (Fakultas Ekonomi Universitas Muhammadiyah Sukabumi, 2020)
This research aims to determine the effect of operating cash flow and fixed asset turnover on return on assets (Case Study In The Telecommunications Sektor Listed in Indonesia Stock Exchange from 2009 to 2013). Variables used in the study conducted by researchers is the operating cash flow and fixed asset turnover as an independent variable and the return on assets as the dependent variable. Population and sample to be taken from the published financial statements and recorded and sourced from PT. Indonesian Capital Market Electronic Library on the Indonesia Stock Exchange. Hypothesis testing in this case. Partially with the t test for the operating cash flow on ROA 5.135 known t> t table 2.026. As for the fixed asset turnover on ROA known 5.174 t> t table 2.206 it means that both of them are parsail affect ROA. The results of the F test is known that simultaneous to the dependent variable indendent known result F 146.421 count> F table 3.251 means that the independent variables simultaneously influence on ROA. The coefficient of determination of 0.888 or 88.8%, which means indepedent variables contribute to the return on assets of 83.9% and the remaining 11.2% is influenced by other factors not examined.